Zingiber officinale Roscoe reduces chest pain on patients undergoing coronary angioplasty: A clinical trial - Afshin Hasanvand; Yahya Ebrahimi; Asghar Mohamadi; Afshin Nazari (Shahrekord University of Medical Sciences, 2019)
Introduction: Evidence from animal studies suggests that Zingiber officinale (ginger) may help prevent ischemia-reperfusion injury (IRI) in heart. The aim of the present study was to investigate the effect of ginger on inducing preconditioning on patients undergoing angioplasty. Methods: Thirty-four patients, referred for elective angioplasty, were randomly divided into the control (17 patients) and ginger groups (17 patients). Subjects in the experimental group were provided 250 mg ginger powder in Zintoma capsules per day for 10 days, whereas those in the control group received placebo. The patients underwent percutaneous transluminal coronary angioplasty (PTCA) (One 45-second balloon inflation and 2 minutes reperfusion). Chest pain scores were assessed immediately after angioplasty and cardiac injury biomarkers were assessed 12 hours later. Results: The average pain score during the balloon inflation in the ginger group was significantly lower than the control group (2.1±1 versus 3.8±1.5, P = 0.04). Troponin I was elevated in both groups after angioplasty, but there was not any significant difference between groups in this regard (P = 0.12 and 0.10, respectively). Conclusion: The use of ginger reduces chest pain during coronary angioplasty but its effect on the release of biochemical markers of myocardial damage is obscure.